The new public health law a transdisciplinary approach to practice and advocacy - Burris, Scott; Berman, Micah L.; Penn, Matthew 1967-; Holiday, Tara Ramanathan (Oxford University Press, 2022)
Newly updated with legal changes in response to COVID-19 and structural racism, 'The New Public Health Law', second edition arms lawyers and public health professionals of any background with the tools to fully exploit the potential of law to improve public health.
Includes bibliographical references and index
Published in print: 1 September 2023
Keywords: Medical policy / United States; Health and Wellbeing; Social services & welfare, criminology